مقام التوبة دراسة فقهيَةّ - Mongy, Nabil Fouly Mohamed (Fatih Sultan Mehmet Vakıf Üniversitesi, 2024)
هل يمكن أن تخضع مسائل التصوف المختصة بأعمال القلب لأحكام فقهية منضبطة شبيهة بتلك التي تحكم أعمال الظاهر؟ حول هذه الإشكالية تأتي هذه الدراسة، مع التطبيق . على مقام التوبة وقد تضمنت الدراسة تعريفا للتوبة، وبيانًا لاصطلاحات شرعية أخرى ذات علاقة بها؛ كالاستغفار والمعصية وما شابههما، وبينت أركانَ التوبة وشروطها وأقسامها، وركزت أكثر . على بيان أحكام التوبة في قضاياها الأساسية والفرعية وترجح من خ لل هذا النموذج البحثي التطبيقي أن نشأة علم يعالج قضايا التصوف في ا عمومها علاجا فقهيا أمر ممكن؛ خاصة أننا نجد التراث الصوفي وغير الصوفي قد طرحا عددا كبيرا من مسائل التصوف بهذه الصفة، وإن كانت متناثرة فيهما.

Tasavvufun kalbin amellerine ait meseleleri, zâhirî amellere ilişkin olanlara benzer bir şekilde düzenlenmiş fıkhî hükümlere tabi tutulabilir mi? Bu çalışma, bu sorunu tevbe makamı üzerinde uygulamalı olarak ele almaktadır. Çalışmada tevbenin tanımı ve tevbeyle ilgili istiğfâr, isyan ve benzeri diğer şerʻî terimlerin açıklamaları yer almaktadır. Yine çalışma tevbenin rükünlerini, şartlarını, kısımlarını açıklamış, tevbenin temel ve ikincil problemlerine dair hükümlerini açıklamaya odaklanmıştır. Bu uygulamalı araştırma örneği ile, tasavvufun genel meselelerini fıkhî bir yaklaşımla ele alan bir ilim dalının ortaya çıkması mümkündür. Özellikle tasavvufî olan ve olmayan mirasın, dağınık da olsa, çok sayıda tasavvufî meseleyi bu nitelikte gündeme getirdiğini görüyoruz.

The station of repentance: A Jurisprudential Approach This applied study endeavors to explore the feasibility of utilizing jurisprudential principles, typically applied to physical acts, to address Islamic mystical issues pertaining to matters of the heart and spirituality. Specifically, it explores “the station of repentance” as an illustrative example. The study begins with an introductory exploration of the concept of repentance, alongside other related notions such as sin and the pursuit of forgiveness. It then proceeds to delineate the fundamental elements and conditions of repentance, including its various types. However, the primary focus lies in an in-depth examination of the jurisprudential rulings concerning issues related to repentance, both fundamental and ancillary. Ultimately, this study concludes that the establishment of a coherent system grounded in Islamic jurisprudence to address spiritual matters within Islamic mysticism is not only feasible but also evident within our tradition through numerous isolated instances, albeit lacking in coherence.
Tevbe Makâmı "Fıkhî İnceleme"
The Station of Repentance: A Jurisprudential Approach
Keywords: فقه; تصوُّف; مقام; التوبة; Fıkıh; Tasavvuf; Makam; Tevbe; Jurisprudence; Mysticism; Spirituality; Station; Repentance